Resposta morfofuncional em tilápia do Nilo (Oreochromis niloticus) através do uso do Núcleo Homeopático Homeopatila 100®. - Braccini, Graciela Lucca (2011)
The effect of Homeopathic Nucleus Homeopatila 100® on the performance, ectoparasite prevalence, and morphological analysis of liver and gills of Nile tilapias (Oreochromis niloticus) of the GIFT strain is evaluated. Performance, ectoparasite prevalence and trichodinid infection category and Dactylogyridae parasite load in the tilapia?s gills and skin were evaluated at the beginning, on the 30th day, and at the end of the experiment. The Homeopathic Nucleus Homeopatila 100® was employed at four concentrations: T1 (control): 20 mL of a hydro-alcohol solution (alcohol 30º GL), T2: 20 mL, T3: 40 mL and T4: 60 mL of Homeopatila 100® per kg of diet, with four repetitions in each treatment, in 16 randomly distributed experimental units, with a density of 40 fish.m-3. The weight and total initial average length of the juveniles were respectively 44.0 ± 7.9 g and 13.1 ± 0.8 cm. Mixed parasitism (55.0%), Monogenoidea (38.0%) and Trichodinids (5.0%) had the highest prevalence. At the end of the assay, the physical and chemical parameters of the water were normal and the fish weight and total average length in all treatments were: T1 (98.5 ± 22.9 g and 17.6 ± 2.8 cm), T2 (99.0 ± 21.7 g and 17.5 ± 2.0 cm), T3 (99.2 ± 16.1 g and 16.1 ± 0.9 cm) and T4 (98.9 ± 20.8 g and 20.8 ± 1.6 cm), respectively. No statistical differences (p<0.05) with regard to results for apparent food conversion and survival were recorded among treatments. Further, no statistical difference (p<0.05) occurred between the total final prevalence of ectoparasites in the different homeopathic treatments, Infestation Category Average by Trichodina and Average Intensity by Monogenoidea, in control and in homeopathic treatments. Although a significant difference occurred in mixed parasitism, with lower results for treatment with Homeopatila 100® at the concentration of 40 mL per kg of diet, high parasitism occurred in the case of Monogenoidea. The morphology of the liver and gills of Nile tilapias fed with the Homeopathic Nucleus Homeopatila 100® was evaluated at the end of the experiment. The liver and gill arches were removed from eight fish in each treatment and standard histological procedures were carried out. Liver samples were weighed and mean liver-body ratios were taken. Histological routine was undertaken for general morphology analysis and for the determination of the number of hepatocytes per area with Hematoxylin-Eosin staining. Schiff's Periodic Acid (PAS) + Hematoxylin histochemical technique was employed to detect intracellular glycogen. Gills were stained with Hematoxylin-Eosin for morphological analysis and Alcian Blue + PAS histochemical technique was used to register neutral and acid mucin-producing cells. RHS of Homeopatila 100®-treated fish was significantly lower (p<0.05) than that of fish in the control group (T1). Best results in liver and gills were recorded in fish treated with Homeopathic Nucleus Homeopatila 100® at the concentration of 40 mL per kg of diet (T3) when number of hepatocytes/mm2, behavior of intracellular glycogen (glycogen-occupied area), histological changes average rates (hyperplasia, lamellar fusion and telangiectasia) and percentage of neutral and acid mucin-producing cells were taken into account (p<0.05). Homeopatila 100® at 40 mL concentration per kg of diet (T3) provided satisfactory results for the performance and parasite prevalence and contributed towards the best morpho-functional response of the liver and gills of juvenile tilapias.